Preparation method and application of beaded aramid nanofiber and composite material thereof
By introducing hydrogen bond donors and silicate compounds on the surface of aramid nanofibers to form a bead-like structure, the problems of uneven distribution of aramid nanofibers in polymers and insufficient interfacial bonding strength are solved, and the composite is significantly improved Material strength and wear resistance.
Patent Information
- Application Number
- CN202211382699.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-11-07
AI Technical Summary
The uneven distribution of aramid nanofibers in matrix materials and weak interface bonding strength, resulting in poor application effect in the field of high-performance polymers. The existing modification methods have industrial problems and insufficient enhancement effects.
By introducing hydrogen bond donors on the surface of aramid nanofibers, forming a beaded structure and modifying it with silicate compounds, uniform beaded aramid nanofibers are creatively prepared under nitrogen protection, improving their polymerization in the polymerization process. dispersion in the object and interface bonding strength.
The uniform beading structure of aramid nanofibers is achieved, which significantly improves the strength, wear resistance and dynamic thermal stability of the composite material, and improves physical and mechanical properties.
Smart Images

Figure CN115652628B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano composite materials, and in particular relates to a preparation method and application of beaded aramid nanofibers and composite materials thereof. Background Art
[0002] Aramid nanofibers retain the structural characteristics of macroscopic aramid fibers with excellent mechanical properties, thermal stability and low density. At the same time, their unique nanoscale is a highly potential "enhanced building block" for constructing high-performance composite materials, which has attracted great attention in the field of nanocomposites.
[0003] Although aramid nanofibers have advantages such as large aspect ratio, high specific surface area, high fiber fineness, good uniformity, and good reinforcement effect on polymers, the nanofiber molecular chain has strong intramolecular and intermolecular hydrogen bonding and π-π stacking effect (amide bond and benzene ring). This special structure makes the fiber prone to flocculation, uneven distribution in the matrix material, and weak interface bonding strength. Therefore, finding a simple, fast, and effective surface functionalization modification technology for aramid nanofibers to improve the interface bonding strength of nano-aramid / polymer composites is of great significance for realizing the application of aramid nanofibers in the field of high-performance polymers.
[0004] The prior art often uses a strong alkaline solution of dimethyl sulfoxide (DMSO) to deprotonate aramid nanofibers, and then enhances and modifies the polymer dissolved in DMSO, or uses it for polymer enhancement after surface chemical modification in a DMSO system. This method uses a strong alkaline solution, which is difficult to post-process, and the concentration of aramid nanofibers in the system is low, which is difficult to achieve industrialization. In order to solve this problem, the prior art uses water-dispersible aramid nanofibers, or uses a silane coupling agent to treat water-dispersible aramid nanofibers, or uses an adhesive to modify the surface of water-dispersible aramid nanofibers, and then co-flocculates with rubber latex to prepare aramid nanofiber reinforced materials. However, these methods need to be further improved in terms of the reinforcing effect on polymers. Summary of the invention
[0005] Based on the above problems, the purpose of the present invention is to provide a new preparation method and application of beaded aramid nanofibers and composite materials thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing beaded aramid nanofibers, the method comprising the following steps:
[0008] (1) Preparation of aramid nanofibers:
[0009] 1) Under nitrogen protection, add polyethylene glycol dimethyl ether and calcium chloride into N-methylpyrrolidone, stir at 400-600 rpm and heat to 100°C to completely dissolve them;
[0010] 2) Cool the reaction system to 0°C, add phenylenediamine monomer and stir until completely dissolved;
[0011] 3) adding a diacyl chloride compound, increasing the stirring speed to 2000 r / min, reacting for 10-30 min, slowly adding the product into high-speed stirred deionized water to obtain an aramid nanofiber dispersion with a concentration of 0.001-0.1%, the high-speed stirring speed is 10000-20000 rpm, and the high-speed stirring time is 5 min;
[0012] 4) subjecting the aramid nanofiber dispersion to 3-5 times of vacuum-assisted filtration and deionized water washing to remove residual reactants and solvents, and finally obtaining an aramid nanofiber gel with a content of 2-5 wt%;
[0013] (2) Preparation of aramid nanofiber hydrogen bond donor solution:
[0014] 1) preparing a hydrogen bond donor into an ethanol solution, adding the aramid nanofiber gel into the hydrogen bond donor solution under stirring, and stirring and mixing to obtain an aramid nanofiber hydrogen bond donor solution;
[0015] (3) Preparation of beaded aramid nanofibers:
[0016] 1) Adding an ethanol solution of a silicate compound dropwise into the aramid nanofiber hydrogen bond donor solution, stirring for 1-4 hours, and filtering and washing the reactants to obtain a beaded aramid nanofiber gel with a content of 2-5 wt%.
[0017] Preferably, in step (1), the concentration of polyethylene glycol dimethyl ether and calcium chloride in NN-methyl pyrrolidone is 0.1-1wt%; the mass ratio of polyethylene glycol dimethyl ether and calcium chloride is 1:(0.9-1.2); the phenylenediamine monomer is p-phenylenediamine or m-phenylenediamine, and the concentration is 2-5wt%; the diacyl chloride compound is terephthaloyl chloride or m-phthaloyl chloride, and the molar ratio with p-phenylenediamine is 1:(1-1.1); the diameter of the aramid nanofiber is 10-30nm.
[0018] Preferably, in step (2), the hydrogen bond donor is an alkoxysilane compound having the following formula I:
[0019]
[0020] In formula I, R is methoxy or ethoxy; at most one of the three Rs is H or alkyl; and R' is one of amino, aminomethyl, aminoethyl, aminopropyl, glycidyloxypropyl, (methacryloyloxy)propyl, N-(2-aminoethyl)-3-aminopropyl, 3-(triethoxysilyl)propylamine, and propylurea.
[0021] Preferably, in step (2), based on 1 mol of amide groups in aramid nanofibers, the amount of hydrogen bond donor is 1-10 mol; the ethanol concentration of the hydrogen bond donor is 0.5-5wt%; the stirring temperature is room temperature, the stirring time is 0.5-2 hours, and the stirring rate is 300-600rpm.
[0022] Preferably, in step (3), the silicate compound is one or a mixture of methyl orthosilicate, ethyl orthosilicate, and bis(trimethoxysilyl)ethane; the molar ratio of the silicate compound to the hydrogen bond donor is (0.5-5):1; the concentration of the ethanol solution of the silicate compound is 10-20wt%; the stirring temperature is room temperature-60°C, and the stirring speed is 300-600rpm.
[0023] Secondly, the present invention provides a beaded aramid nanofiber, which is prepared by the preparation method according to any one of claims 1-5.
[0024] Secondly, the present invention provides a method for preparing a beaded aramid nanofiber composite material, characterized in that the preparation method comprises the following steps:
[0025] (1) The beaded aramid nanofiber gel is uniformly dispersed in a dispersion, a polymer is added during stirring at 300-600 rpm at room temperature to prepare a pre-dispersion, and a beaded aramid nanofiber composite material is obtained after flocculation and drying.
[0026] Preferably, the dispersion is a good solvent for the polymer or deionized water; the polymer is solid rubber, plastic or latex; the concentration of the beaded aramid nanofiber in the dispersion is 0.001-1wt%; the mass ratio of the polymer to the aramid nanofiber is 1:(0.005-0.2); the stirring temperature is 20-60°C, and the stirring time is 1-24 hours; the flocculation method includes steam stripping, calcium chloride or sodium chloride aqueous solution flocculation, and ethanol flocculation; the drying method includes vacuum drying and air drying, and the drying temperature is room temperature-60°C.
[0027] Secondly, the present invention provides a beaded aramid nanofiber composite material, which is prepared by the preparation method according to any one of claims 7-8.
[0028] Secondly, the present invention provides the application of beaded aramid nanofibers, and the beaded aramid nanofibers can be used as reinforcing materials in the field of polymer reinforcement.
[0029] In addition, the present invention provides an application of the beaded aramid nanofiber composite material, and the beaded aramid nanofiber composite material is used as a reinforcing material in the field of polymer reinforcement.
[0030] The beneficial effects of the present invention are:
[0031] In the preparation method provided by the present invention, hydrogen bonds are creatively added to induce the nucleation and in-situ growth of nanoparticles on the surface of aramid nanofibers, so that the obtained beaded aramid nanofibers have a uniform beaded structure and a uniform particle size distribution;
[0032] At the same time, compared with the modified aramid nanofibers without added hydrogen bond donors, a uniform beaded structure cannot be formed without the action of hydrogen bond donors;
[0033] In addition, compared with unmodified aramid nanofibers and aramid nanofiber composites without hydrogen bond donor modification, the beaded aramid nanofiber composite material prepared by the present invention has significantly improved strength, wear resistance and dynamic heat generation, and has excellent comprehensive physical and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a transmission electron microscope spectrum of the beaded aramid nanofibers prepared in Example 1;
[0035] Figure 2 This is the transmission electron microscope spectrum of the aramid nanofiber prepared in Comparative Example 1;
[0036] Figure 3 The thermogravimetric analysis of the unmodified aramid nanofibers, the beaded aramid nanofibers prepared in Example 1, and the aramid nanofibers prepared in Comparative Example 1;
[0037] Figure 4 This is a scanning electron microscope spectrum of the cross section of the tensile specimen of the beaded aramid nanofiber rubber composite material prepared in Example 3;
[0038] Figure 5 This is a scanning electron microscope spectrum of the cross-section of the tensile specimen of the unmodified aramid nanofiber rubber composite material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0039] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.
[0040] The range endpoints and any values disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0041] In the following examples and comparative examples:
[0042] 1. The microstructure of the nanofibers was measured using a JEM-2100 transmission electron microscope (manufactured by JEOL Ltd, Japan).
[0043] 2. Thermogravimetric analysis The measurement was performed using a TGA 2 thermogravimetric analyzer (manufactured by METTLER TOLEDO Ltd, USA) with a heating rate of 10 K / min, a temperature range of room temperature to 900° C., and a nitrogen atmosphere.
[0044] 3. The SEM spectra of the polymer composites were measured using a JSM7500F scanning electron microscope (manufactured by JEOL Ltd, Japan), and the test sample was the cross section of the tensile specimen.
[0045] 3. The tensile strength and modulus of the polymer composites were measured using a Model Z005 electronic tensile testing machine (manufactured by Zwick Ltd, Germany) in accordance with DIN 53504, with a tensile speed of 500 mm / min and a temperature of room temperature.
[0046] 4. The wear properties of polymer composites were measured using a DIN abrasion machine (manufactured by High Speed Rail Technology Co., Ltd.) in accordance with DIN 53516.
[0047] 5. The dynamic properties of the polymer composites were measured using a GABO EPlexor 500N dynamic mechanical analyzer (manufactured by NETSCH Ltd, Germany) in the tensile mode with a temperature scanning range of -70-80°C, a strain of 0.5%, and a frequency of 10 Hz.
[0048] Example 1
[0049] (1) Add 100 mL of NMP to a reaction vessel and heat to 100° C. under nitrogen. Add 0.2 g of calcium chloride and 0.2 g of polyethylene glycol dimethyl ether and stir at 100° C. and 300 rpm for 30 minutes.
[0050] (2) The reaction vessel was placed in an ice-water mixture and cooled to 0°C, and 2.16 g of p-phenylenediamine was added;
[0051] (3) Add 4.26 g of terephthaloyl chloride to the system, increase the stirring speed to 2000 r / min, react for 20 min, and then add 300 mL of deionized water;
[0052] (4) Pour the reactants into a high-speed stirrer at 10,000 rpm and stir for 5 min to form an ANF dispersion with a concentration of 0.1%;
[0053] (5) the product was subjected to vacuum assisted filtration and deionized water washing for three times to remove residual reactants and solvents, and finally an aramid nanofiber gel with a content of 2.7 wt% was obtained;
[0054] (6) 18.52 g of aramid nanofiber gel was added to 200 mL of ethanol, and 3 mL of 3-aminopropyltriethoxysilane was added during stirring at room temperature, and stirred at 300 rpm for 60 minutes;
[0055] (7) Disperse 2 mL of tetraethyl orthosilicate in 10 mL of ethanol, add the mixture to the reaction system, and continue stirring for 3 hours;
[0056] (8) Vacuum assisted filtration was performed and the mixture was thoroughly washed with ethanol for 5 times. Finally, a beaded aramid nanofiber gel with a solid content of 3.2 wt% was obtained.
[0057] The transmission electron microscope photo of the beaded aramid nanofiber prepared by the method of the present invention is as follows: Figure 1 As shown. Figure 1 It can be seen that there is an obvious beaded structure on the surface of the aramid nanofiber. The diameter of the beaded structure is about 50nm, the morphology is uniform, and the coverage rate on the surface of the aramid nanofiber is high.
[0058] The beaded aramid nanofibers prepared by the method of the present invention were subjected to thermogravimetric analysis ( Figure 3 ), the content of beaded microspheres was 20.1wt%.
[0059] Example 2
[0060] (1) Add 100 mL of NMP to a reaction vessel and heat to 100° C. under nitrogen. Add 0.2 g of calcium chloride and 0.2 g of polyethylene glycol dimethyl ether and stir at 100° C. and 300 rpm for 30 minutes.
[0061] (2) Place the reaction vessel in an ice-water mixture and cool to 0°C, then add 2.16 g of p-phenylenediamine. Finally, add 4.26 g of terephthaloyl chloride to the system, increase the stirring speed to 2000 r / min, and add 300 mL of deionized water after reacting for 20 min.
[0062] (3) Pour the reactants into a high-speed stirrer at 10,000 rpm and stir for 5 min to form an ANF dispersion with a concentration of 0.1%;
[0063] (4) the product was subjected to vacuum assisted filtration and deionized water washing for three times to remove residual reactants and solvents, and finally an aramid nanofiber gel with a content of 2.7 wt% was obtained;
[0064] (5) 18.52 g of aramid nanofiber gel was added to 200 mL of ethanol, and 3 mL of 3-glycidyloxypropyltriethoxysilane was added during stirring at room temperature, and stirred at 300 rpm for 60 minutes;
[0065] (6) adding 25 wt % ammonia water to adjust the pH to be the same as in Example 1;
[0066] (7) Disperse 2 mL of tetraethyl orthosilicate in 10 mL of ethanol, add the mixture to the reaction system, and continue stirring for 3 hours;
[0067] (8) Vacuum assisted filtration was performed and the mixture was thoroughly washed with ethanol for 5 times. Finally, a beaded aramid nanofiber gel with a solid content of 2.8 wt% was obtained.
[0068] The surface of the beaded aramid nanofiber prepared by the method of the invention has an obvious beaded structure, the diameter of the beaded structure is 50-80nm, and the coverage rate on the surface of the aramid nanofiber is high.
[0069] The content of the beaded microspheres was found to be 22.3 wt % by thermogravimetric analysis of the beaded aramid nanofibers prepared by the method of the present invention.
[0070] Comparative Example 1
[0071] (1) Add 100 mL of NMP to a reaction vessel and heat to 100° C. under nitrogen. Add 0.2 g of calcium chloride and 0.2 g of polyethylene glycol dimethyl ether and stir at 100° C. and 300 rpm for 30 minutes.
[0072] (2) The reaction vessel was placed in an ice-water mixture and cooled to 0°C, and 2.16 g of p-phenylenediamine was added;
[0073] (3) Add 4.26 g of terephthaloyl chloride to the system, increase the stirring speed to 2000 r / min, react for 20 min, and then add 300 mL of deionized water;
[0074] (4) Pour the reactants into a high-speed mixer at 10,000 rpm and stir for 5 min to form an ANF dispersion with a concentration of 0.1%;
[0075] (5) the product was subjected to vacuum assisted filtration and deionized water washing for three times to remove residual reactants and solvents, and finally an aramid nanofiber gel with a content of 2.7 wt% was obtained;
[0076] (6) 18.52 g of aramid nanofiber gel was added to 200 mL of ethanol, and 25 wt % of ammonia water was added dropwise during stirring at room temperature to adjust the pH value to be the same as in Example 1, and the mixture was stirred at 300 rpm for 60 minutes;
[0077] (7) Disperse 2 mL of tetraethyl orthosilicate in 10 mL of ethanol, add the mixture to the reaction system, and continue stirring for 3 hours;
[0078] (8) Vacuum assisted filtration was performed and the mixture was thoroughly washed with ethanol for 5 times. Finally, a beaded aramid nanofiber gel with a solid content of 2.1 wt.% was obtained.
[0079] The transmission electron microscope photo of the beaded aramid nanofiber prepared by the method of the present invention is as follows: Figure 2 As shown. Figure 2 It can be seen that the aramid nanofibers cannot form a uniform beaded structure and the nanoparticle sizes vary greatly.
[0080] The modified aramid nanofibers prepared by the method of the present invention were subjected to thermogravimetric analysis ( Figure 3 ) to obtain a microsphere content of 25.9wt%.
[0081] Example 3
[0082] (1) 0.5 phr of beaded ANFs were dispersed in 500 mL of xylene, and the mixture was stirred at room temperature for 1 hour to form a uniform dispersion;
[0083] (2) 50 g of solution-polymerized styrene-butadiene rubber (SBR) was added to the dispersion. After mechanical stirring for 12 hours, the mixture was stripped to recover the solvent, and then vacuum dried at 40° C. for 72 hours to obtain a beaded aramid nanofiber composite material.
[0084] (3) A green tire tread rubber formula was used for mixing in an internal mixer, and the formula was as follows: SBR / ANFs 100.5 phr (including beaded ANFs 0.5 phr); white carbon black 40 phr; naphthenic oil 10 phr; TESPT 4 phr; zinc oxide 3 phr; stearic acid 1 phr; N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine 2 phr; microcrystalline wax 1 phr; N-cyclohexylbenzothiazole-2-sulfoxide 1.6 phr; diphenylguanidine 1.5 phr; sulfur 2 phr;
[0085] (4) mixing in an internal mixer using a two-step method. In the first stage, after rubber, zinc oxide, stearic acid, antioxidant, silicon dioxide and silane are added to the internal mixer, the mixing temperature is increased to 150±5°C and maintained for 3 minutes;
[0086] (5) In the second stage, vulcanizing agent is added to the mixing mill. After the mixed rubber is left for 24 hours, the vulcanization time at 160°C is measured by a vulcanizer;
[0087] (6) Finally, a flat plate vulcanizer is used to prepare the vulcanized rubber. The tensile strength of the rubber is 15.0 MPa, the 300% elongation stress is 12.5 MPa, and the DIN abrasion is 0.061 cm 3 , the loss factor at 60°C is 0.077.
[0088] Depend on Figure 4 Scanning electron microscopy of the tensile cross section shows that the beaded aramid nanofibers are evenly dispersed in the polymer matrix.
[0089] Example 4
[0090] (1) A beaded aramid nanofiber composite material was prepared according to the method of Example 3, except that the amount of beaded nanofiber added to the composite material was 1 phr.
[0091] The test results show that the tensile strength of the rubber is 18.4MPa, the 300% elongation stress is 13.1MPa, and the DIN abrasion is 0.067cm 3 , the loss factor at 60°C is 0.078.
[0092] Example 5
[0093] (1) 10 phr of beaded ANFs were dispersed in 1000 mL of xylene, and the mixture was stirred at room temperature for 1 hour to form a uniform dispersion;
[0094] (2) adding solution polymerized styrene butadiene rubber (50 g) to the dispersion. After mechanical stirring for 12 hours, the mixture was stripped to recover the solvent, and then vacuum dried at 40°C for 72 hours to obtain a beaded aramid nanofiber pre-dispersion;
[0095] (3) Mixing in an internal mixer, the formula is as follows: SBR 95phr; aramid predispersion 5.5phr; white carbon black 40phr; naphthenic oil 10phr; TESPT 4phr; zinc oxide 3phr; stearic acid 1phr; N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine 2phr; microcrystalline wax 1phr; N-cyclohexylbenzothiazole-2-sulfoxide 1.6phr; diphenylguanidine 1.5phr; sulfur 2phr;
[0096] (4) mixing in an internal mixer using a two-step method. In the first stage, after rubber, zinc oxide, stearic acid, antioxidant, aramid pre-dispersion, silica and silane are added to the internal mixer, the mixing temperature is increased to 150±5°C and maintained for 3 minutes;
[0097] (5) In the second stage, a vulcanizing agent is added to an open mixing mill. After the mixed rubber is left standing for 24 hours, the vulcanization time at 160°C is measured by a vulcanizer. Finally, a flat plate vulcanizer is used to prepare the vulcanized rubber.
[0098] The test results show that the tensile strength of the rubber is 15.1MPa, the 300% elongation stress is 12.3MPa, and the DIN abrasion is 0.060cm 3 , the loss factor at 60°C is 0.077.
[0099] Example 6
[0100] (1) 0.5 phr of beaded ANFs were dispersed in 100 mL of deionized water, and the dispersion was dripped into natural rubber latex (solid content 50 g) drop by drop, mechanically stirred for 1 hour, and the mixture was dripped into 1.5 wt % calcium chloride aqueous solution and continued to be stirred for 1 hour. After filtering, it was dried in a vacuum oven at 40 ° C for 72 hours to obtain a beaded aramid nanofiber composite material;
[0101] (2) Mixing in an internal mixer, the formula is as follows: NR / ANFs 100.5phr (including beaded ANFs 0.5phr); white carbon black 40phr; naphthenic oil 10phr; TESPT 4phr; zinc oxide 3phr; stearic acid 1phr; N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine 2phr; microcrystalline wax 1phr; N-cyclohexylbenzothiazole-2-sulfoxide 1.6phr; diphenylguanidine 1.5phr; sulfur 2phr;
[0102] (3) mixing in an internal mixer using a two-step method. In the first stage, after rubber, zinc oxide, stearic acid, antioxidant, silicon dioxide and silane are added to the internal mixer, the mixing temperature is increased to 150±5°C and maintained for 3 minutes;
[0103] (4) In the second stage, vulcanizing agent is added to the mixing mill. After the mixed rubber is left for 24 hours, the vulcanization time at 160°C is measured by a vulcanizer;
[0104] (5) Finally, a flat plate vulcanizer is used to prepare the vulcanized rubber.
[0105] The test results show that the tensile strength of the rubber is 29.5MPa, the 300% elongation stress is 23.5MPa, and the DIN abrasion is 0.065cm 3 , the loss factor at 60°C is 0.069.
[0106] Example 7
[0107] (1) A beaded aramid nanofiber composite material was prepared according to the method of Example 6, except that the amount of beaded nanofiber added to the composite material was 1 phr.
[0108] The test results show that the tensile strength of the rubber is 32.1MPa, the 300% elongation stress is 24.2MPa, and the DIN abrasion is 0.063cm 3 , the loss factor at 60°C is 0.074.
[0109] Example 8
[0110] (1) 10 phr of beaded ANFs were dispersed in 500 mL of deionized water, and the dispersion was dripped into natural rubber latex (solid content 50 g) drop by drop, mechanically stirred for 1 hour, and the mixture was dripped into 1.5 wt % calcium chloride aqueous solution and continued to be stirred for 1 hour. After filtering, it was dried in a vacuum oven at 40° C. for 72 hours to obtain a beaded aramid nanofiber predispersion;
[0111] (2) Mixing in an internal mixer, the formula is as follows: NR 95phr; aramid predispersion 5.5phr; white carbon black 40phr; naphthenic oil 10phr; TESPT 4phr; zinc oxide 3phr; stearic acid 1phr; N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine 2phr; microcrystalline wax 1phr; N-cyclohexylbenzothiazole-2-sulfoxide 1.6phr; diphenylguanidine 1.5phr; sulfur 2phr;
[0112] (3) mixing in an internal mixer using a two-step method. In the first stage, after rubber, zinc oxide, stearic acid, antioxidant, aramid pre-dispersion, silica and silane are added to the internal mixer, the mixing temperature is increased to 150±5°C and maintained for 3 minutes;
[0113] (4) In the second stage, a vulcanizing agent is added to the mixing mill. After the mixed rubber is left for 24 hours, the vulcanization time at 160°C is measured using a vulcanizer.
[0114] (5) Finally, a flat plate vulcanizer is used to prepare the vulcanized rubber.
[0115] The test results show that the tensile strength of the rubber is 30.0MPa, the 300% elongation stress is 24.5MPa, and the DIN abrasion is 0.065cm 3 , the loss factor at 60°C is 0.070.
[0116] Comparative Example 2
[0117] (1) Mixing was performed in an internal mixer, and no aramid nanofiber was added to the formula, and the formula was as follows: SBR 100phr; white carbon black 40phr; naphthenic oil 10phr; TESPT 4phr; zinc oxide 3phr; stearic acid 1phr; N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine 2phr; microcrystalline wax 1phr; N-cyclohexylbenzothiazole-2-sulfoxide 1.6phr; diphenylguanidine 1.5phr; sulfur 2phr;
[0118] (2) mixing in an internal mixer using a two-step method. In the first stage, after rubber, zinc oxide, stearic acid, antioxidant, silicon dioxide and silane are added to the internal mixer, the mixing temperature is increased to 150±5°C and maintained for 3 minutes;
[0119] (3) In the second stage, a vulcanizing agent is added to the mixing mill, and the mixed rubber is left for 24 hours, and then the vulcanization time at 160°C is measured by a vulcanizer;
[0120] (4) Finally, a flat plate vulcanizing machine is used to prepare the vulcanized rubber.
[0121] The test results show that the tensile strength of the rubber is 14.2MPa, the 300% elongation stress is 7.4MPa, and the DIN abrasion is 0.076cm 3 , the loss factor at 60°C is 0.086.
[0122] Comparative Example 3
[0123] (1) An aramid nanofiber composite material was prepared according to the method of Example 3, except that unmodified aramid nanofibers were used in the composite material instead of the beaded aramid nanofibers.
[0124] The test results show that the tensile strength of the rubber is 14.4MPa, the 300% elongation stress is 10.0MPa, and the DIN abrasion is 0.076cm 3 , the loss factor at 60°C is 0.083.
[0125] Depend on Figure 5 Scanning electron microscopy of the tensile section shows that the unmodified aramid nanofibers show obvious agglomeration in the polymer matrix.
[0126] Comparative Example 4
[0127] An aramid nanofiber composite material was prepared according to the method of Example 4, except that unmodified aramid nanofibers were used in the composite material instead of the beaded aramid nanofibers.
[0128] The test results show that the tensile strength of the rubber is 15.5MPa, the 300% elongation stress is 10.2MPa, and the DIN abrasion is 0.083cm 3, the loss factor at 60°C is 0.093.
[0129] Comparative Example 5
[0130] Aramid nanofiber predispersion was prepared according to the method of Example 5, except that unmodified aramid nanofibers were used instead of beaded aramid nanofibers in the composite material.
[0131] The test results show that the tensile strength of the rubber is 14.0MPa, the 300% elongation stress is 10.0MPa, and the DIN abrasion is 0.077cm 3 , the loss factor at 60°C is 0.086.
[0132] Comparative Example 6
[0133] An aramid nanofiber composite material was prepared according to the method of Example 6, except that unmodified aramid nanofibers were used in the composite material instead of the beaded aramid nanofibers.
[0134] The test results show that the tensile strength of the rubber is 25.3MPa, the 300% elongation stress is 18.5MPa, and the DIN abrasion is 0.078cm 3 , the loss factor at 60°C is 0.080.
[0135] Comparative Example 7
[0136] An aramid nanofiber composite material was prepared according to the method of Example 7, except that unmodified aramid nanofibers were used in the composite material instead of the beaded aramid nanofibers.
[0137] The test results show that the tensile strength of the rubber is 25.0MPa, the 300% elongation stress is 17.9MPa, and the DIN abrasion is 0.081cm 3 , the loss factor at 60°C is 0.089.
[0138] Comparative Example 8
[0139] An aramid nanofiber composite material was prepared according to the method of Example 8, except that unmodified aramid nanofibers were used in the composite material instead of the beaded aramid nanofibers.
[0140] The test results show that the tensile strength of the rubber is 25.0MPa, the 300% elongation stress is 17.1MPa, and the DIN abrasion is 0.076cm 3 , the loss factor at 60°C is 0.081.
[0141] The strength, wear resistance and dynamic performance of the rubber composite materials of the above embodiments and comparative examples are shown in Table 1.
[0142] Table 1 Comparison of strength, wear resistance and dynamic performance of rubber composite materials of embodiments and comparative examples
[0143]
[0144]
[0145] It can be seen from the above results that, compared with the unmodified aramid nanofibers, the beaded aramid nanofibers prepared by the present invention can effectively improve the physical, mechanical and dynamic properties of the composite material; and compared with Example 2 (no aramid nanofibers added), Example 3 (adding 0.5phr beaded aramid nanofibers) can further increase the 300% tensile stress of the filler-reinforced polymer composite by 69%, improve the wear resistance by 20%, and improve the dynamic properties at the same time (rolling resistance is reduced by 10.5%).
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing beaded aramid nanofibers, characterized in that: The preparation method comprises the following steps: (1) Preparation of aramid nanofibers: 1) Under nitrogen protection, add polyethylene glycol dimethyl ether and calcium chloride into N-methylpyrrolidone, stir at 400-600 rpm and heat to 100°C to completely dissolve them; 2) Cool the reaction system to 0°C, add phenylenediamine monomer and stir until completely dissolved; 3) Adding a diacyl chloride compound, increasing the stirring speed to 2000 r / min, reacting for 10-30 min, slowly adding the product into high-speed stirred deionized water to obtain an aramid nanofiber dispersion with a concentration of 0.001-0.1%, the high-speed stirring speed is 10000-20000 rpm, and the high-speed stirring time is 5 min; 4) subjecting the aramid nanofiber dispersion to vacuum filtration and deionized water washing for 3-5 times to remove residual reactants and solvents, and finally obtaining an aramid nanofiber gel with a content of 2-5 wt%; (2) Preparation of aramid nanofiber hydrogen bond donor solution: 1) preparing a hydrogen bond donor solution using an ethanol solution as a hydrogen bond donor, adding the aramid nanofiber gel to the hydrogen bond donor solution under stirring conditions, and stirring and mixing the mixture to obtain an aramid nanofiber hydrogen bond donor solution; (3) Preparation of beaded aramid nanofibers: 1) adding an ethanol solution of a silicate compound dropwise into the aramid nanofiber hydrogen bond donor solution, stirring for 1-4 hours, and filtering and washing the reactant to obtain a beaded aramid nanofiber gel with a content of 2-5wt%; The hydrogen bond donor is 3-aminopropyltriethoxysilane or 3-glycidyloxypropyltriethoxysilane.
2. The preparation method according to claim 1, characterized in that: In step (1), the concentration of polyethylene glycol dimethyl ether and calcium chloride in N-methyl pyrrolidone is 0.1-1wt%; the mass ratio of polyethylene glycol dimethyl ether to calcium chloride is 1:(0.9-1.2); the phenylenediamine monomer is p-phenylenediamine or m-phenylenediamine, and the concentration is 2-5wt%; the diacyl chloride compound is terephthaloyl chloride or m-phthaloyl chloride, and the molar ratio with p-phenylenediamine is 1:(1-1.1); the diameter of the aramid nanofiber is 10-30nm.
3. The preparation method according to claim 2, characterized in that: In step (2), based on 1 mol of amide groups in aramid nanofibers, the amount of hydrogen bond donor is 1-10 mol; the concentration of the hydrogen bond donor solution is 0.5-5wt%; the stirring temperature is room temperature, the stirring time is 0.5-2 hours, and the stirring rate is 300-600rpm.
4. The preparation method according to claim 3, characterized in that: In step (3), the silicate compound is one or a mixture of methyl orthosilicate, ethyl orthosilicate, and bis(trimethoxysilyl)ethane; the molar ratio of the silicate compound to the hydrogen bond donor is (0.5-5):1; the concentration of the ethanol solution of the silicate compound is 10-20wt%; the stirring temperature is room temperature-60°C, and the stirring speed is 300-600rpm.
5. A beaded aramid nanofiber, characterized in that: The beaded aramid nanofiber is prepared by the preparation method according to any one of claims 1 to 4.
6. A method for preparing a beaded aramid nanofiber composite material, characterized in that: The preparation method comprises the following steps: (1) uniformly dispersing the beaded aramid nanofiber gel in a dispersion, adding a polymer during stirring at 300-600 rpm at room temperature to prepare a pre-dispersion, and obtaining a beaded aramid nanofiber composite material after flocculation and drying; The beaded aramid nanofiber gel is prepared by the preparation method described in any one of claims 1-4.
7. The preparation method according to claim 6, characterized in that: The dispersion is a good solvent for the polymer or deionized water; the polymer is solid rubber, plastic or latex; the concentration of the beaded aramid nanofiber gel in the dispersion is 0.001-1wt%; the mass ratio of the polymer to the beaded aramid nanofiber gel is 1:(0.005-0.2); the stirring time is 1-24 hours; the flocculation method includes steam stripping, calcium chloride or sodium chloride aqueous solution flocculation, and ethanol flocculation; the drying method includes vacuum drying and air drying, and the drying temperature is room temperature-60°C.
8. A beaded aramid nanofiber composite material, characterized in that: The beaded aramid nanofiber composite material is prepared by the preparation method according to any one of claims 6-7.
9. The use of the beaded aramid nanofibers according to claim 5, characterized in that: The beaded aramid nanofiber can be used as a reinforcing material in the field of polymer reinforcement.
Citation Information
Patent Citations
Preparation method of SiO2 aerogel composite material doped with aramid fibre
CN101823867A
Nanometer aramid fiber modified nitrile butadiene rubber and preparation method thereof
CN110204806A